2021
DOI: 10.2147/ijn.s325697
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Synergistic Activity of Zolmitriptan Combined in New Self-Nanoemulsifying Drug Delivery Systems: ATR-FTIR Real-Time Fast Dissolution Monitoring and Pharmacodynamic Assessment

Abstract: Purpose The current work aimed to overcome the poor permeability and undesirable adverse effects of Zolmitriptan (ZMT) and to increase its efficacy in the treatment of acute migraine by exploiting the synergistic effect of the essential oil, lavender, to fabricate ZMT self-nanoemulsifying drug delivery systems (ZMT-SNEDDS). Methods ZMT-SNEDDS were fabricated based on full factorial design (3 2 ) to statistically assess the impact of oil and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…A small number of SEDDS-based products have already been successfully introduced into the pharmaceutical market, with none of them loading drugs for the treatment of neurological disorders. Until now, several in vivo assays using oral SEDDS have been carried out for neuropharmaceuticals brain targeting [ 4 , 6 , 23 , 24 , 25 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 70 ], but only a few in vivo pre-clinical studies have been reported for IN administration of neurotherapeutics loaded in SEDDS. In fact, only six studies were found that investigated the IN administration of neurotherapeutics loaded in SEDDS: clonazepam [ 45 ], diazepam [ 44 ], and perampanel [ 28 ] for epilepsy treatment; Bdph for glioblastoma treatment [ 4 ]; huperzine A [ 30 ] for Alzheimer’s disease; and naringin [ 5 ] as a neuroprotective for Alzheimer’s and Parkinson’s disease.…”
Section: Application Of Sedds In Brain Drug Delivery—pre-clinical Stu...mentioning
confidence: 99%
See 3 more Smart Citations
“…A small number of SEDDS-based products have already been successfully introduced into the pharmaceutical market, with none of them loading drugs for the treatment of neurological disorders. Until now, several in vivo assays using oral SEDDS have been carried out for neuropharmaceuticals brain targeting [ 4 , 6 , 23 , 24 , 25 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 70 ], but only a few in vivo pre-clinical studies have been reported for IN administration of neurotherapeutics loaded in SEDDS. In fact, only six studies were found that investigated the IN administration of neurotherapeutics loaded in SEDDS: clonazepam [ 45 ], diazepam [ 44 ], and perampanel [ 28 ] for epilepsy treatment; Bdph for glioblastoma treatment [ 4 ]; huperzine A [ 30 ] for Alzheimer’s disease; and naringin [ 5 ] as a neuroprotective for Alzheimer’s and Parkinson’s disease.…”
Section: Application Of Sedds In Brain Drug Delivery—pre-clinical Stu...mentioning
confidence: 99%
“…In Table 2 , it can also be observed that the majority of the here-reviewed compounds belong to BCS class II or IV, similar to most chemical entities investigated to treat neurological disorders [ 6 , 7 ]. Only zolmitriptan [ 46 ], ginsenoside Rg1 [ 47 ], and chlorogenic acid [ 48 ] are reported to belong to BCS class III.…”
Section: Application Of Sedds In Brain Drug Delivery—pre-clinical Stu...mentioning
confidence: 99%
See 2 more Smart Citations
“…The mean VS, PDI, and ZP of the various fabricated CBE loaded BSALs were examined using Malvern Zetasizer (Abd El-Halim et al., 2021 ).…”
Section: In Vitro Characterization and Optimization Of Cbe Loaded Bsalsmentioning
confidence: 99%